Sense of Coherence and Caregiver Burden Among Informal Caregivers of People with Dementia in China: The Mediating Role of Coping Strategies - Long D; Gu Y; Wang Y (Psychology Research and Behavior Management, 2025)
Dechao Long,1– 3 Yanhong Gu,1– 3 Yang Wang1– 3 1Nursing Department, Shanghai Fifth People’s Hospital, Fudan University, Shanghai, People’s Republic of China; 2School of Nursing, Fudan University, Shanghai, People’s Republic of China; 3Center of Community-Based Health Research, Fudan University, Shanghai, People’s Republic of ChinaCorrespondence: Yanhong Gu, Nursing Department, Shanghai Fifth People’s Hospital, Fudan University, Shanghai, People’s Republic of China, Email reddy_gu@163.comBackground: This study aimed to explore the relationship between SOC, coping strategies, and caregiver burden, and analyze the mediating role of coping strategies in the relationship between SOC and caregiver burden.Methods: A cross-sectional study was carried out, involving 230 informal caregivers of people with dementia in Shanghai, China. The data collection period is May 21, 2024, to December 31, 2024. This study involved participants who filled out various questionnaires, encompassing demographic data, Sense of Coherence Scale (SOC-13), Brief COPE inventory, and Zarit Burden Interview (ZBI). Adoption of SPSS 27.0 for statistical analysis and Hayes’ PROCESS (Model 4), and the mediating effect was validated by the bias-corrected nonparametric percentile bootstrap method.Results: The caregiver burden was found at a moderate to severe level with the average score of 58.14(12.84). There was a negative correlation between SOC and caregiver burden (r = − 0.655, P< 0.05), a positive correlation between SOC and emotion-focused coping strategies (r = 0.397, P< 0.05), and a negative correlation between SOC and dysfunctional coping strategies (r = − 0.513, P< 0.05). However, there was no significant correlation between SOC and problem-focused coping strategies. The relationship between SOC and caregiver burden was partially mediated by emotion-focused strategies and dysfunctional coping strategies.Conclusion: Significant relationship was found that SOC correlated with caregiver burden; To some extent, emotion-focused and dysfunctional coping strategies moderated the relationship between SOC and caregiver burden. Future interventions could focus on adapting and optimizing the coping behaviors of informal caregivers, using mediating mechanisms as entry points, with the aim of achieving more precise and effective care support.Keywords: caregiver burden, dementia, informal caregivers, sense of coherence, coping strategies